Exploration of the Mechanism of the Control of Coccidiosis in Chickens Based on Network Pharmacology and Molecular Docking With the Addition of Modified Gegen Qinlian Decoction - Peng, Xiaomin; Wang, Kaijun; Wang, Yuhan; Lu, Yujie; Lv, Feifei; Cui, Yao; Wang, Ying; Si, Hongbin (Frontiers in Veterinary Science, 2022)
Gegen Qinlian Decoction is a long-established Chinese herbal compound for the treatment of diarrhea and dysentery, while Magnolia officinalis has been demonstrated to have some anthelmintic activity. The preliminary screening of this study showed that the addition of Modified Gegen Qinlian Decoction has some effective on the prevention and treatment of coccidiosis in chickens. However, the mechanism of its treatment of chicken coccidiosis is not clear. The network pharmacology study was based on the screening of chemical components and related targets from TCMSP and PharmMapper server databases. Genes related to chicken coccidiosis were obtained from the SRA database, and those genes that intersected with the target genes of Modified Gegen Qinlian Decoction were screened. By exploring the target interactions through the String system and enrichment analysis by the Metascape system, the mechanism of action of Modified Gegen Qinlian Decoction in chicken coccidiosis was identified. Using real-time quantitative polymerase chain reaction (RT-qPCR) to analyze the mRNA levels of the relevant factors in chicken coccidiosis, molecular docking was used to reveal the extent of binding of the key target genes predicted in the network pharmacology by the action of Modified Gegen Qinlian Decoction. Compound and target screening suggested that the 99 chemical targets of Modified Gegen Qinlian Decoction were involved in chicken coccidiosis, and the enrichment results of KEGG pathway suggested that Modified Gegen Qinlian Decoction was significantly associated with PI3K/AKT signaling pathway in chicken coccidiosis. The Hubba gene module in Cytoscape_v3.7.1 software was used to analyze the network topology to obtain the Hubba gene SRC, STAT3, and PPARG, etc. The molecular docking results showed that SRC, STAT3, and PPARG were key targets in the treatment of coccidiosis in chickens by Modified Gegen Qinlian Decoction, which was in agreement with the RT-qPCR results. Through network pharmacology, molecular docking and in vitro experiments, it was confirmed that Modified Gegen Qinlian Decoction fights against chicken coccidiosis through key targets such as SRC, STAT3, and PPARG.